Out‐of‐plane buckled cantilever microstructures with adjustable angular positions using thermal bimorph actuation for transducer applications. (1st October 2015) - Arevalo, Arpys; Conchouso, David; Castro, David; Diaz, Marlon; Foulds, Ian G.
Abstract : The integration of thermal bimorph actuators and buckled cantilever structures to form an out‐of‐plane plate with adjustable angular positions is reported. This structure could be used as a platform to build other transducers such as optical micromirrors, scanning antennas, switches or low‐frequency oscillators. The electromechanical characterisation has shown that these structures can adjust their angular position by 6° when they are operated using a DC source. The thermal characterisation performed by an infrared camera showed that the heat‐affected zone reaches a maximum temperature of 125°C while the rest of the structure remains unaffected by the generated heat.